1988
DOI: 10.1128/jvi.62.8.2531-2536.1988
|View full text |Cite
|
Sign up to set email alerts
|

B- and T-lymphocyte responses to an immunodominant epitope of human immunodeficiency virus

Abstract: Using synthetic peptides, we characterized the B-lymphocyte (antibody) and T-lymphocyte (proliferation) responses to an immunodominant epitope of human immunodeficiency virus type 1 (HIV-1) located near the amino-terminal end of the transmembrane glycoprotein (env amino acids 598 to 609). Both immunoglobulin M (IgM) and IgG antibodies against this epitope appeared early after primary infection with HIV-1. In an animal model, the IgG response to a synthetic peptide derived from this sequence was T-helper-cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…Schrier et at. [20] reported that a 26-mer gp4l peptide {aa 584-609). which included the whole sequence of our immunodominant 12-mcr gp41|8!…”
Section: Discussionmentioning
confidence: 99%
“…Schrier et at. [20] reported that a 26-mer gp4l peptide {aa 584-609). which included the whole sequence of our immunodominant 12-mcr gp41|8!…”
Section: Discussionmentioning
confidence: 99%
“…obtained from control sera. n = 132 n = 28 n = 160 [Wang et al, 1986;Gnann et al, 1987a;Gnann et al, 1987b;Smith et al, 1987;Narvanen et al, 1988;Schrier et al, 1988;Shafferman et al, 19891. Surprisingly, only 50% of the sera from HIV-1 infected Tanzanians recognized this epitope.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we selected synthetic peptides that represented variable and conserved regions of gp160 among different HIV-1 isolates. The peptides have been previously shown to define HIV-1 gp160 epitopes based on recognition by antibodies from HIV-1 infected individuals and/or inducing anti-HIV-1 gp160 responses when immunized into experimental animals [Chanh et al, 1986;Kennedy et al, 1986;Wang et al, 1986;Gnann et al, 1987aGnann et al, , 1987bHo et al, 1987;Palker et al, 1987Palker et al, , 1988Smith et al, 1987;Narvanen et al, 1988;Schrier et al, 1988;Dope1 et al, 1989;Schafferman et al, 1989;Cease, 1990;Warren et al, 19901. Reactivity of HIV-1 sera from Tanzania to peptides 425-448, 616-632, and 735-752 that define 1 gp120 and 2 gp41 epitopes, respectively, was shown to be weak (less than 6%).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, enhanced asymmetry between conditions for immune stimulation and antigen removal facilitates elimination of pathogens. Conversely, pathogens evolve immunodominance [67] and make fitness-restoring mutations [68] that increase R act and decrease R inh , both of which aid in evasion.…”
Section: Discussionmentioning
confidence: 99%